EDUCATING THE IMPACT OF GADGET USE ON THE ETHICS OF WR SUPRATMAN 1 MEDAN HIGH SCHOOL STUDENTS - Manik, Desma Erica Maryati; Nainggolan, Elisabeth; Loo, Petrus (Smart Education, 2025)
Abstract: Information technology is currently developing rapidly. Gadgets as a form of technological development is a common tool used by all circles. Gadgets such as smartphones, tablets or laptops allow users to search for any information instantly via the internet. In the world of education, the presence of these gadgets can have both positive and negative impacts on students. Through gadgets, students can learn online, access e-books, watch educational videos and attend online classes. Gadgets facilitate communication through text messaging, voice calls, video calls and social media anytime and anywhere. Students can interact with teachers through apps like Zoom and Google Meet. Despite their benefits in terms of information access and learning, unwise use can affect students' behaviour and ethics, such as lack of manners, dependence on social media, and reduced in-person social interaction. Through this activity, students of SMA WR Supratman 1 Medan were given an understanding of the benefits and risks of using gadgets, as well as how to use them wisely and responsibly. The education was delivered by a team of STIE Eka Prasetya lecturers through interactive lectures, discussions, and case studies. The results of the activity showed that participants gained an increased understanding and awareness of the importance of maintaining ethics in the daily use of technology. Keyword: technology, gadgets, ethics Abstrak: Teknologi informasi saat ini berkembang dengan pesat. Gadget sebagai salah satu bentuk perkembangan teknologi merupakan alat yang umum digunakan oleh semua kalangan. Gadget seperti smartphone, tablet, atau laptop memungkinkan penggunanya untuk mencari informasi apapun secara instan melalui internet. Dalam dunia pendidikan, kehadiran gadget ini dapat memberikan dampak positif dan negatif bagi pelajar. Melalui gadget, pelajar dapat belajar secara online, mengakses e-book, menonton video edukasi, dan mengikuti kelas online. Gadget memfasilitasi komunikasi melalui pesan teks, panggilan suara, panggilan video, dan media sosial kapan saja dan di mana saja. Pelajar dapat berinteraksi melalui aplikasi seperti Zoom dan Google Meet dengan guru. Meskipun memberikan manfaat dalam hal akses informasi dan pembelajaran, penggunaan yang tidak bijak dapat mempengaruhi perilaku dan etika pelajar, seperti kurangnya sopan santun, ketergantungan terhadap media sosial, serta menurunnya interaksi sosial langsung. Melalui kegiatan ini, pelajar SMA WR Supratman 1 Medan diberikan wawasan mengenai manfaat dan risiko penggunaan gadget, serta cara menggunakannya secara bijak dan bertanggung jawab. Edukasi disampaikan oleh tim dosen STIE Eka Prasetya melalui ceramah interaktif, diskusi, dan studi kasus. Hasil kegiatan menunjukkan bahwa peserta memperoleh peningkatan pemahaman dan kesadaran akan pentingnya menjaga etika dalam penggunaan teknologi sehari-hari. Kata kunci: teknologi, gadget, etika